Selling The Region: The Problems of a Multi‐Agency Approach in Promoting Regional Economies. Issue 3 (5th March 2020) - Crawley, Andrew; Munday, Max; Delbridge, Rick
Abstract: The institutional landscape for promoting regions for foreign inward investment continues to evolve across all nations. In the UK the abandonment of regional development agencies has led to years of institutional flux and uncertainty. One nation in the UK, Wales has seen the most dramatic changes in structure. The Welsh Development Agency was arguably one of the most successful in the world but was abolished in 2006 and has seen no direct replacment. This paper carries out a qualitative investigation over a 6 year period analyzing stages in the process of promoting of region. The paper examines how the loss of a strong coordinating marketing agency, and an evolving multi‐agency approach creates problems. The paper also explores whether the framework of organisational fields developed in organisation theory might provide a means of understanding how the evolving multi‐agency approach to inward investment attraction can be highly problematic. The findings have implications applicable for any region promoting itself for inward investment. Resumen: El panorama institucional para la promoción de las regiones para atraer la inversión extranjera sigue evolucionando en todas las naciones. En el Reino Unido, el abandono de las agencias de desarrollo regional ha dado lugar a años de cambios institucionales e incertidumbre. Una nación en el Reino Unido, el País de Gales, ha experimentado los cambios estructurales más dramáticos. Se puede argumentar que la Agencia de Desarrollo de País de Gales fue una de las más exitosas del mundo, pero fue abolida en 2006 y no ha sido sustituida con algo equivalente. Este artículo realiza una investigación cualitativa sobre un período de 6 años mediante el análisis de las etapas del proceso de promoción de la región. El artículo explora los problemas creados por la pérdida de una poderosa agencia de coordinación en mercadotecnia y su reemplazo por un enfoque cambiante que hace uso de múltiples agencias. El artículo también examina si el marco de las áreas organizativas desarrollado por la teoría de la organización podría proporcionar un medio para entender cómo un enfoque cambiante que hace uso de múltiples agencias puede ser muy problemático para la atracción de la inversión exterior. Las conclusiones tienen implicaciones aplicables a cualquier región que se promocione para atraer la inversión exterior. 抄録: 外国からの対内投資を目的とした地域振興のための制度的環境が、すべての国で発展し続けている。英国では、地域開発庁の廃止により、制度の流動化と不確実性が何年も続いている。連合王国の一国であるウェールズは、最も劇的な構造的変化を遂げてきた。ウェールズ開発庁(Welsh Development Agency)は間違いなく世界で最も成功を収めた機関のひとつであるが、2006年に廃止されて以来、直接的にこれに代わる機関は設立されていない。本稿では、地域振興のプロセスの段階を分析した6年間の定性的調査を実施する。調整役となる強力なマーケティングを行う機関の喪失と、複数の機関による進化的アプローチがどのように問題を生じさせるかを検討する。また、対内投資を誘導する複数の機関による進化的アプローチがいかに問題を生じやすくするかを理解する方法が、組織理論で作られた組織フィールドのフレームワークによりもたらされるかどうかについても検討する。本研究の知見は、対内投資のため地域振興を推進するすべての地域に当てはまるものである。